Effect of protein and/or carbohydrate fractions of dried whey on performance and nutrient digestibility of weanling pigs - Tokach, Michael D.; Nelssen, Jim L.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and eighty 3-wk old pigs (initial weight 10.6 lb) were utilized in a 35-day growth trial to determine the effects of the carbohydrate and/or protein fractions of dried whey on pig performance. In addition, 30 3-wk-old pigs (initial weight 10.8 lb) were used in two digestion trials to study the effects of the whey fractions on nutrient digestibility. Dietary treatments included a corn-soybean meal control (CON), control + 20% dried whey (WHE), control + 14% lactose (CHO), control + 2.1% lactalbumin (PRO), control + 14% lactose + 2.1% lactalbumin (CHO + PHD), and control + 8.4% whey protein concentrate (WPC). Diets were pelleted and balanced on an isolysine basis. Lactose and lactalbumin were added at the same levels as provided by a 20% dried whey diet. Pigs fed diets containing milk products exhibited superior average daily gain; feed efficiency; and apparent dry matter, energy, and nitrogen digestibility (P(.05) compared to pigs fed the control diet. These results indicate that both the carbohydrate (lactose) and protein (lactalbumin) fractions of dried whey are important in explaining the beneficial response to dried whey elicited by the weanling pig.
Keywords: Swine